Acute spinal subdural hematoma following lumbar puncture in a pediatric leukemia patient - Kheirreddine Mohamed Abderraouf; Khelifa Adel; Aichaoui Fayçal; Morsli Abdelhalim (Journal of Current Research in Scientific Medicine)
Acute spinal subdural hematoma (ASSDH) is a rare complication following intrathecal chemotherapy; however, it has the potential to cause significant morbidity. We present the case of a child treated with intrathecal chemotherapy for acute myeloid leukemia. The child presented with pain and acute paralysis in the lower limbs a few hours after lumbar puncture. Radiological findings confirmed the presence of ASSDH. The child was operated on after correcting severe thrombocytopenia. Postoperatively, the patient experienced relief from pain; however, there was no noticeable improvement in motor deficit immediately, and postoperative imaging confirmed total evacuation of the hematoma, and intensive rehabilitation was prescribed. ASSDH is a rare complication of lumbar puncture that physicians should consider, especially in leukemic patients, after correcting all hemostasis parameters; diagnosis is based on clinical presentation and radiological findings, and management requires neurosurgical intervention.